Low‐ and middle‐income country abstract representation at the Society for Maternal Fetal Medicine Annual Pregnancy Meeting. Issue 3 (22nd June 2021) - Kazma, Jamil M.; Saleeb, Monica; Potarazu, Savita; Stringer, Elizabeth; Ahmadzia, Homa K.; Gimovsky, Alexis C.
Synopsis: The representation of LMICs in SMFM meetings is limited. Most abstracts presented are retrospective analyses.